Instructional Model for Multicultural Islamic Education in Digital High Schools : Systematic Literature Review - Sukma Eka Saputra; Mambaul Ngadhimah (Attractive : Innovative Education Journal, 2025)
This study aims to examine the urgency, identify the challenges, and reformulate (reframe) multicultural Islamic Religious Education (PAI) in the context of secondary school learning in facing the phenomenon of digital polarization. The approach used is a systematic literature review (SLR) with conceptual-thematic analysis based on the PRISMA framework of 21 selected articles that specifically focus on the context of secondary education, gathered from the Scopus database within the period 2016–2026. This study is also reinforced by fundamental literature related to Islamic education, multiculturalism, digital literacy, and algorithmic culture. The results reveal three main findings. First, digital polarization not only causes fragmentation of religious discourse but also drives a shift in authority to the digital space and strengthens tendencies toward exclusivism, thus requiring a reorientation of PAI towards dialogical, reflective, and inclusive learning. Second, the development of multicultural PAI faces multidimensional challenges that include epistemological aspects (the dominance of textual-doctrinal approaches), pedagogical aspects (limited critical digital literacy and teachers’ dialogical capacities), as well as structural aspects (the influence of algorithmic culture that creates echo chambers and cognitive biases). Third, a comprehensive strategy is needed, encompassing the reconstruction of the PAI paradigm, the development of an integrative curriculum based on multiculturalism and critical digital literacy, the design of dialogical-participatory learning, the strengthening of teacher competencies, and cross-stakeholder collaboration. This study produces an integrative and adaptive instructional design model for multicultural PAI, covering components of learning challenges, instructional interventions, stages of the learning process, as well as learning outcomes and assessments. This model provides practical contributions as an operational framework for the development of PAI curriculum and learning design that is responsive to the dynamics of digital polarization.